2021
DOI: 10.3389/fpsyt.2021.648713
|View full text |Cite
|
Sign up to set email alerts
|

Electroencephalographic Parameters Differentiating Melancholic Depression, Non-melancholic Depression, and Healthy Controls. A Systematic Review

Abstract: Introduction: The objective of this systematic review was to investigate whether electroencephalographic parameters can serve as a tool to distinguish between melancholic depression, non-melancholic depression, and healthy controls in adults.Methods: A systematic review comprising an extensive literature search conducted in PubMed, Embase, Google Scholar, and PsycINFO in August 2020 with monthly updates until November 1st, 2020. In addition, we performed a citation search and scanned reference lists. Clinical … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 43 publications
0
5
0
Order By: Relevance
“…Given the known heterogeneity of depression and the issues raised in differential diagnosis ( Ghaemi and Vöhringer, 2011 ; Fried, 2017 ; Lorenzo-Luaces et al, 2021 ), reliable objective criteria such as electroencephalography (EEG) indices would have been helpful in detecting and differentiating depressive states. Currently, there is no consensus in the meta-analytic literature regarding the discriminative power of EEG asymmetry in depression, or in symptoms associated with depression, some highlighting the marker’s ability to discriminate ( Bruun et al, 2021 ), while others concluding inconsistencies, based on existing evidence ( van der Vinne et al, 2017 ; Kaiser et al, 2018 ; Kołodziej et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…Given the known heterogeneity of depression and the issues raised in differential diagnosis ( Ghaemi and Vöhringer, 2011 ; Fried, 2017 ; Lorenzo-Luaces et al, 2021 ), reliable objective criteria such as electroencephalography (EEG) indices would have been helpful in detecting and differentiating depressive states. Currently, there is no consensus in the meta-analytic literature regarding the discriminative power of EEG asymmetry in depression, or in symptoms associated with depression, some highlighting the marker’s ability to discriminate ( Bruun et al, 2021 ), while others concluding inconsistencies, based on existing evidence ( van der Vinne et al, 2017 ; Kaiser et al, 2018 ; Kołodziej et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…Afterwards the individual ratings were compared, and any controversy was discussed with a third author (LVK). The STROBE scores were divided into percentages with ≤33% points reflecting low study quality, 33%–66% reflecting moderate study quality and ≥66% reflecting high study quality in accordance with prior procedures 20 …”
Section: Methodsmentioning
confidence: 99%
“…The STROBE scores were divided into percentages with ≤33% points reflecting low study quality, 33%-66% reflecting moderate study quality and ≥66% reflecting high study quality in accordance with prior procedures. 20…”
Section: Risk Of Bias Of Individual Studiesmentioning
confidence: 99%
“…The search for neurobiological correlates of melancholia has included studies of the electrical activity of the brain [ 16 ], sometimes collected via an electroencephalograph (EEG) [ 17 ], which measures electrical activity at sites across the skull, enabling inferences to be drawn regarding brain activity under those sites. However, Bruun et al [ 17 ] found that some methodological limitations in much of the previous research on the neurobiological correlates of melancholia have left this issue yet to be comprehensively resolved.…”
Section: Introductionmentioning
confidence: 99%